PERKEMBANGAN BENTUK PENYAJIAN DAN FUNGSI EINE KLEINE NACHTMUSIK K.525 KARYA WOLFGANG AMADEUS MOZART - HS, Irwan Rizki (Harmonia: Journal of Arts Research and Education, 2009)
Wolfgang Amadeus Mozart is a genius figure and professionals in the field of musiccomposition. In addition to a composition he is also an expert in playing musicalinstruments, violin and harpsichord. He have many works of instrumental musiccomposition, vocal, even to the form of a symphony orchestra with choir produced. Somegreat works that have been created is a composition for string quartet chamber music.Eine Kleine Nachtmusik K.525 is one of his works, which is still often heard in thecorners of the world. The composition of this string quartet has a character andcharacteristics of light music and lively, so well known in the community. In this case, theauthor tried to assess Eine Kleine Nachtmusik in the development and function of thepresentation is still sound and well-known in this modern era. To discuss this paper usedqualitative methods with descriptive analysis, the approach to musicology. The results ofthis paper is the development and function of serving an increasingly wide of the formand format of presentation of original work.Kata Kunci: Musik, Eine Kleine Nachtmusik K.525, W.A Mozart